2000
DOI: 10.1111/j.1572-0241.2000.02265.x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of subclinical hepatic encephalopathy

Abstract: The prognostic significance of subclinical hepatic encephalopathy appears limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(65 citation statements)
references
References 17 publications
2
61
1
1
Order By: Relevance
“…Similar results had been achieved years before by Hartmann et al [26]. They studied 116 patients of whom 25 were diagnosed with mHE using the NCTA, digit symbol test and EEG.…”
Section: Prognosissupporting
confidence: 63%
“…Similar results had been achieved years before by Hartmann et al [26]. They studied 116 patients of whom 25 were diagnosed with mHE using the NCTA, digit symbol test and EEG.…”
Section: Prognosissupporting
confidence: 63%
“…In three recent studies [15,17,18], MHE in combination with liver dysfunction was related to the development of overt HE in long-term follow-up. MHE had been diagnosed using a combination of three psychometric tests that had proved useful in previous reports [19].…”
Section: Discussionmentioning
confidence: 96%
“…However, its prognostic value has been demonstrated in many other situations involving cirrhosis over the last 30 years. In particular, multivariate analyses using Child-Pugh score as an entity have shown that it has an independent prognostic value in the settings of ascites [13], ruptured oesophageal varices [14], subclinical encephalopathy [15], hepatocellular carcinoma [16], liver surgery [17], alcoholic cirrhosis [18], decompensated HCV-related cirrhosis [19], primary sclerosing cholangitis [20], primary biliary cirrhosis [21] and Budd-Chiari syndrome [22].…”
Section: Validationmentioning
confidence: 99%